Biological and Climate Controls on North Atlantic Marine Carbon Dynamics Over the Last Millennium: Insights From an Absolutely Dated Shell-Based Record From the North Icelandic Shelf - Reynolds, DJ; Hall, IR; Scourse, JD; Richardson, CA; Wanamaker, AD; Butler, PG (Global Biogeochemical Cycles, 2017)
This is the final version of the article. Available from Wiley via the DOI in this record. Given the rapid increase in atmospheric carbon dioxide concentrations (pCO 2 ) over the industrial era, there is a pressing need to construct long-term records of natural carbon cycling prior to this perturbation and to develop a more robust understanding of the role the oceans play in the sequestration of atmospheric carbon. Here we reconstruct the past biological and climate controls on the carbon isotopic (δ 13 C shell ) composition of the North Icelandic shelf waters over the last millennium, derived from the shells of the long-lived marine bivalve mollusk Arctica islandica. Variability in the annually resolved δ 13 C shell record is dominated by multidecadal variability with a negative trend (−0.003 ± 0.002‰ yr −1 ) over the industrial era (1800–2000 Common Era). This trend is consistent with the marine Suess effect brought about by the sequestration of isotopically light carbon (δ 13 C of CO 2 ) derived from the burning of fossil fuels. Comparison of the δ 13 C shell record with Contemporaneous proxy archives, over the last millennium, and instrumental data over the twentieth century, highlights that both biological (primary production) and physical environmental factors, such as relative shifts in the proportion of Subpolar Mode Waters and Arctic Intermediate Waters entrained onto the North Icelandic shelf, atmospheric circulation patterns associated with the winter North Atlantic Oscillation, and sea surface temperature and salinity of the subpolar gyre, are the likely mechanisms that contribute to natural variations in seawater δ 13 C variability on the North Icelandic shelf. Contrasting δ 13 C fractionation processes associated with these biological and physical mechanisms likely cause the attenuated marine Suess effect signal at this locality. We thank the members of the R/V Bjarni Sæmundsson (Cruise No. B05-2006). This work was supported by the NERC-funded ULTRA project (grant NE/H023356/1), NERC-funded ...